Implementation of vaginal cleansing prior to cesarean delivery to decrease endometritis rates. (18th June 2019) - Felder, Laura; Paternostro, Amanda; Quist-Nelson, Johanna; Baxter, Jason; Berghella, Vincenzo
Abstract: Background: Endometritis is a postpartum complication that is more common after cesarean delivery. It frequently requires intravenous antibiotic administration, prolonged hospital stays, and carries a risk of sepsis or abscess formation. Precesarean vaginal preparation has been shown to decrease the risk of endometritis in patients who have labored or have ruptured membranes. Objective: The objective of this study was to assess the practical implementation of a protocol for vaginal cleansing prior to cesarean delivery and the subsequent effect on endometritis rates in a clinical setting. Study design: This is a before–after retrospective cohort study evaluating the first 6 months of implementation of a vaginal cleansing protocol at a single institution. The primary outcome was the rate of implementation. Secondary outcomes included endometritis and other postoperative complications. Results: The rate of implementation after 6 months was 68.3% ( p  < .001) and postoperative endometritis rates decreased from 14.0% before implementation to 11.7% after implementation ( p .49, OR 0.77, CI 0.36–1.62). Postoperative fever decreased from 22.3% to 18.3% ( p .256, OR 0.70, CI 0.37–1.30) and infectious wound complications were 4.5% and 5.8%, respectively ( p .76, OR 1.07, CI 0.69–3.64). Conclusions: Implementation of a protocol for vaginal cleansing prior to cesarean delivery in women with ruptured membranes or in labor has high uptake, but in almost a third of eligible women it was not performed. The implementation, has led to a clinical, although not statistical, decrease in postoperative endometritis. Continued research is needed to explore how to improve uptake of this quality improvement measure.